Effects of sports training & nutrition on bone mineral density in young Indian healthy females - Marwaha, Raman K. (Medknow Publications, 2011)
BACKGROUND & OBJECTIVES: Peak bone mass, a major determinant of osteoporosis is influenced by genetic, nutritional, lifestyle and hormonal factors. This study was designed to evaluate the impact of sports training on dietary intake and bone mineral and metabolic parameters in young healthy Indian females. METHODS: Healthy female college going students (N=186, sportswomen, 90; controls 96) in the age group of 18-21 yr, residing in New Delhi (India) were evaluated for anthropometry, biochemistry (serum total and ionic calcium, phosphorus, total alkaline phosphatase, 25-hydroxyvitamin D & parathyroid hormone), diet, physical activity and lifestyle. Bone mineral density (BMD) at hip, forearm and lumbar spine were studied using central DXA. RESULTS: Sports related physical activity (3 vs. 0 h/day, P<0.001) and direct sunlight exposure (120 vs. 30 min/day, P<0.001) were significantly higher in sportswomen than in controls with sedentary lifestyle. Significantly higher intake of all macronutrients (energy, protein, carbohydrates and fat) and dietary calcium was noted in the diets of sportswomen. Mean serum 25(OH)D levels were significantly higher (53.0±18.9 vs. 12.9±7.7 nmol/l; P<0.001) while PTH (35.3±17.6 vs. 51.7±44.9 pg/ml; P<0.001) and ALP levels (194.0±51.0 vs. 222.1±51.4 IU/l; P<0.001) were significantly lower in sportswomen when compared to controls. No significant difference was found in ionized calcium and inorganic phosphorus in the two groups. Significantly higher (P<0.001) total BMD and BMD at all sites except femur neck were found in sportswomen than controls (P<0.001). INTERPRETATION & CONCLUSIONS: Physical activity, optimal nutrition and adequate sun exposure are vital for attaining peak bone mass.